Leveraging Digital Twins for ON/OFF-LINE Blockchain Networks: A Resilient Framework for Drone and IoT Communication - Park, Seong Su; Kim, Ki Hyung (International Conference on Information Networking, 2025)
In this paper, we propose a novel framework for leveraging digital twins to enhance ON/OFF-LINE blockchain networks in drone and IoT communication systems. The proposed solution addresses critical challenges in environments where internet connectivity is intermittent or restricted, such as construction sites, remote areas, or military operations. We present a resilient communication architecture that integrates Digital Twins (DTs) to mirror the state of offline blockchain nodes in the cloud, enabling efficient synchronization and reducing data conflicts when transitioning between online and offline states. The framework also introduces a method for efficient data management and secure, decentralized identity verification by using packaged certification with DID documents and selfcontained verifiable credentials. By maintaining a synchronized digital twin in the cloud, the proposed system ensures that offline nodes can operate independently while seamlessly integrating updates when connectivity is restored.
Keywords: Block-chain; Communications systems; Critical challenges; Decentralised; Decentralized ID; DID; Internet connectivity; IoT; Offline; Offline certification; Blockchain; Decentralized ID; DID; Digital Twins; IoT; Offline certification